Applications of In Ovo Technique for the Optimal Development of the Gastrointestinal Tract and the Potential Influence on the Establishment of Its Microbiome in Poultry - Roto, Stephanie M.; Kwon, Young Min; Ricke, Steven C. (Frontiers in Veterinary Science, 2016)
As the current poultry production system stands, there is a period of time that newly hatched chicks are prevented from access to feed for approximately 48 to 72 hours. Research has indicated that this delay in feeding may result in decreased growth performance when compared to chicks that are fed immediately post-hatch. To remedy this issue, in ovo methodology may be applied in order to supply the embryo with additional nutrients prior to hatching and that those nutrients will continue to be utilized by the chick post-hatch during the fasting period. Furthermore, in ovo injection of various biologics have been researched based on the ability of not only supplying the chick embryo with additional nutrients that would promote improved growth, but also compounds that may benefit the future health of the chicken host. Such compounds include various immunostimulants, live beneficial bacteria, prebiotics, and synbiotics. However, it is important to determine the site and age of the in ovo injection for the most productive effects. The primary focus of the current review is to address these two issues (the most effective site(s) and age(s) of in ovo injection) as well as provide the framework for the development of the gastrointestinal tract (GIT) of the chick embryo. Additionally, recent research suggests the colonization of the microbiota in the developing chick may occur during the late stages of embryogenesis. Therefore, we will also discuss the potentials of the in ovo injection method in establishing a healthy and diverse community of microorganisms to colonize the developing GIT that will provide both protection from pathogen invasion as well as improved growth performance to developing chicks.